PENGARUH SOFT SKILLS DAN HARD SKILL TERHADAP INOVASI GURU SEKOLAH ISLAM - Evy Yanthy; Rachma Nadhila Sudiyono; Hatoli Waruwu; Eva Agistiawati; Agus Purwanto (Universitas Muria Kudus, 2020)
This study aims to measure the effect of hard skills and soft skills on the innovation abilities of Islamic school teachers in Jakarta and Tangerang which are mediated by organizational culture. Data collection is done by simple random sampling via electronic to the teacher population in Jabodetabek. The returned and valid questionnaire results were 667 samples. Data processing using SEM method with SmartPLS 3.0 software.The results of this study conclude that hard skills and soft skills have a positive and significant effect on the ability of teacher innovation, both directly and indirectly through mediating organizational culture. This study proposes a model for building the innovation ability of Islamic school teachers among teachers in Jakarta and Tangerang through enhancing hard skills and soft skills with organizational culture as a mediator. This research can pave the way to improve teacher readiness in facing the era of education 4.0.